KOORDINASI NONPLAYER CHARACTER FOLLOWER MENGGUNAKAN ALGORITMA POTENTIAL FIELDS BERBASIS MULTIBEHAVIOUR - Latius Hermawan; Mochamad Hariadi; Ruri Suko Basuki (Jurnal Teknologi Informasi - Cyberku (JTIC), 2017)
Games have become popular among the people, as a form of entertainment, social support interaction between them . NPC behavior modeling is an important issue in realizing the intelligence of computer games . In NPC team - mate, AI needed to help regulate the behavior of team - mate who played alongside or under the command of a human player to assist players in achieving the goal. Potential fields is described as the iron particles are moving towards the object through the magnetic field created by the target object . This movement depends on the existing magnetic field , the particles will be drawn towards the goal , or just the opposite of the iron particles will be rejected by the magnetic field at the time met an obstacle . In this study , the data obtained by reading the references relating to the title to find out the problems faced in coordinating the team in the game . From the study , analyzed the needs of the games that will be made to the AI model that will be used for team coordination . Only then designed a game that can resolve the issue . After the game was made , the game will be tested by several methods , so it will look the difference . The expected outcome of this study is to model the NPC behavior Follower and adjust the position of the player in accordance with the AI have been made . So players will not quickly lose the game and can finish coordinate with the NPC Follower followed by adjusting the movement of NPC Follower to the players during the attacks , NPC Follower still within range radius of the player to protect the player